2005
DOI: 10.1111/j.1365-2044.2005.04223.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for Caesarean section and neonatal acid‐base status: a meta‐analysis*

Abstract: SummarySpinal anaesthesia is generally preferred for Caesarean section. Its superiority for the baby is often assumed. Umbilical artery acid-base status provides a valid index of fetal welfare. Twenty-seven studies reporting neonatal acid-base data with different types of anaesthesia were used to compare umbilical artery or vein pH and base deficit, using random-effect meta-analysis. Cord pH was significantly lower with spinal than with both general (difference: )0.015; 95% CI )0.029 to )0.001; 13 studies, 127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
3
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(147 citation statements)
references
References 95 publications
4
132
3
8
Order By: Relevance
“…Preservative-free morphine is also available at an appropriate dilution (2 mg in 10 ml); 0.1 mg (0.5 ml of this solution) provides comparable postoperative analgesia to diamorphine 0.25 mg [23]. Obsessive maintenance of left-lateral tilt to offset aortocaval compression and prompt use of phenylephrine (now widely regarded as the vasopressor of choice) should mitigate the slight fetal acidosis that has been observed after spinal compared with epidural or general anaesthesia [24,25]. Preload (administration of fluid before spinal anaesthesia) has been superseded by 'coload' -a fluid bolus coinciding with the sympathetic blockade.…”
Section: Epidural Top-upmentioning
confidence: 99%
“…Preservative-free morphine is also available at an appropriate dilution (2 mg in 10 ml); 0.1 mg (0.5 ml of this solution) provides comparable postoperative analgesia to diamorphine 0.25 mg [23]. Obsessive maintenance of left-lateral tilt to offset aortocaval compression and prompt use of phenylephrine (now widely regarded as the vasopressor of choice) should mitigate the slight fetal acidosis that has been observed after spinal compared with epidural or general anaesthesia [24,25]. Preload (administration of fluid before spinal anaesthesia) has been superseded by 'coload' -a fluid bolus coinciding with the sympathetic blockade.…”
Section: Epidural Top-upmentioning
confidence: 99%
“…Spinal anaesthesia is the preferred mode of anaesthesia for elective caesarean delivery 1,2 . Benefits include avoiding the risks involved during general anaesthesia such as difficult intubation and aspiration of gastric contents 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Apgar and neonatal neurobehavioral scores are relatively insensitive measures of neonatal well-being, and umbilical cord blood gas and pH measurements may reflect an obstetric bias (indication for the cesarean delivery rather than differences in anesthetic techniques). Some previous studies have found that umbilical artery pH was greater in the neonate delivered with general anesthesia, but clinical parameters (e.g., Apgar score and the need for assisted ventilation) were better when regional anesthesia was used [28]. The acidemia found following regional anesthesia seems to be increased after spinal as compared to epidural anesthesia, but has not been related to any clinically significant neonatal complication [20,28].…”
Section: Regional Versus General Anesthesia: What Are the Main Evidenmentioning
confidence: 92%